Fazlur Rahman's Concept of Thought "Islam and Modernity" - Edi Sungkowo, (International Journal of Scientific Research and Management (IJSRM), 2022)
Islamic education has an important position in internalizing religious values in society in a country. From here it is important that the development of Islamic education in maintaining the balance of physical and spiritual education. In its journey, Islamic education experienced a fairly rapid development. Many figures contributed their thoughts to the world of education, especially Islamic education. One of the most phenomenal figures in Islamic education and modernity is fazlur rahman. This research aims to explore the concept of educational thought fazlur rahman, especially about Islam and Modernity. Rahman's thoughts emphasize in his work entitled Ismal and Modernity, will absolutely require the synthesis of material in the teachings of the Qur'an. Without this effort, it will be able to result in the application of qur'an verses separately and individually which can result in misdirection. According to fazlur rahman, to convert and recite the Qur'an, a study of historical aspects is needed by providing a presentation of problems in the present in the contest where the Qur'an is revealed.